Self-healing Concrete and Environmental Health - Mehrdad Amiri; Javad Majrouhi Sardroud; Ali Golsoorat Pahlaviani (Shahrekord University of Medical Sciences, 2018)
Nanotechnology will serve as a suitable solution to achieve high performance in future construction. Using this new technology results in creativity and innovation in the construction industry. One of these new technologies is the smart concrete which has received much emphasis in recent years. Many research and experiments have been conducted in scientific research centers around the world in this regard. It is an undeniable fact that concrete structures are prone to cracking. Natural processes have caused cracks in the concrete through which harmful substances entered the concrete leading to steel corrosion. To tackle this issue through the conventional method of concrete restorative, materials, especially polymers which are also harmful to the environment, are used. An alternative that the scientists have achieved is to employ bacteria in concrete through which to produce self-healing concrete and also to reduce the problems regarding the maintenance of concrete for the environment. Bacteria contribute to the durability and performance of the concrete and increase the service life of the concrete.